Adolescent Binge Alcohol Enhances Early Alzheimer’s Disease Pathology in Adulthood Through Proinflammatory Neuroimmune Activation - Barnett, Alexandra; David, Emeraghi; Rohlman, Aaron; Nikolova, Viktoriya D.; Moy, Sheryl S.; Vetreno, Ryan P.; Coleman, Leon G. (Frontiers in Pharmacology, 2022)
Epidemiological studies suggest that heavy alcohol use early in life is associated with increased risk for Alzheimer’s disease (AD) (Mukamal et al., 2003, Langballe et al., 2015). However, mechanisms connecting AD with alcohol use have not been identified. Both heavy alcohol use and AD feature increased proinflammatory signaling. Therefore, we hypothesized that adolescent binge ethanol would increase AD molecular and behavioral pathology in adulthood through proinflammatory signaling. The 3xTg-AD mouse model (APPSwe, tauP301, Psen1tm1Mpm) which features amyloid (Aβ) and tau pathology beginning at 6-12 months underwent adolescent intermittent ethanol (AIE, 5g/kg/d, i.g., P25-55) with assessment of AD pathologic mediators at P200. A second group of mice received AIE +/- minocycline (30mg/kg/d, IP) followed by behavioral testing in adulthood. Behavioral testing and age of testing included: locomotor activity and exploration (27-28 wks), novel object recognition (NORT, 28-30wks), 3-chamber sociability and social memory (29-31 wks), prepulse inhibition (PPI, 30-32 wks), Morris Water Maze with reversal (MWM, 31-35 wks), and Piezo sleep monitoring (35-37 weeks). We found that AIE increased levels of neurotoxic Aβ1-42 in adult female hippocampus as well as intraneuronal Aβ1-42 in amygdala and entorhinal cortex. Phosphorylated tau at residue Thr181 (p-tau-181) was also increased in female hippocampus by AIE. Several proinflammatory genes were persistently increased by AIE in the female hippocampus, including IL-1β, MCP-1, IL-6, and IFNα. Expression of these genes was strongly correlated with the levels of Aβ1-42 and p-tau-181 in hippocampus. AIE caused persistent decreases in locomotor activity (open-field and NORT habituation) and increased anxiety-like behavior (thigmotaxis) while reducing memory retention. Treatment with the anti-inflammatory compound minocycline during AIE blocked persistent increases in Aβ1-42 in amygdala and p-tau-181 in hippocampus, and prevented AIE-induced thigmotaxis and memory loss. Together, these data find that adolescent binge ethanol enhances AD molecular and behavioral pathology in adulthood through proinflammatory signaling. Blockade of proinflammatory signaling during ethanol exposure prevents ethanol-induced effects on pathologic accumulation of AD-associated proteins and persistent behavior changes relevant to human AD.